The prosodification of possessive enclitics in Airola and Boiano - De Sisto, Mirella; Torres-Tamarit, Francesc (Moderna Språk, 2020)
In southern Italian dialects, possessives have an enclitic variant typically associated with kinship nouns (Rohlfs 1967, Sotiri 2007, Ledgeway 2009, D’Alessandro & Migliori 2017) (e.g. [ˈfratə-mə] ˈbrother myˈ). The most common strategy to avoid violations of the three-syllable window is to avoid the enclitic form of the possessive, or stress shift, as in Lucanian (e.g. [ˌiennəˈru-mə] cf. [ˈiennərə], Lüdtke 1979:31). In the dialects of Airola and Boiano, a different strategy is attested: with proparoxytonic nouns (e.g. [ˈjennərə] ˈson-in-lawˈ in both varieties and [ˈsɔtʃəra]/[ˈswotʃəra] ˈmother/father-in-lawˈ in Boiano), the last unstressed syllable of the host is deleted (e.g. [ˈjennə-mə], [ˈsɔtʃə-mə], [ˈswotʃə-mə]). We claim that possessive enclitics in Airola and Boiano are internal clitics, that is, they amalgamate with the prosodic word that contains the host noun. We further propose that both proparoxytonic stress and the three-syllable-window derive from internally layered ternary feet (Martínez-Paricio 2013). These feet need to be aligned with the right edge of their containing prosodic word. When a possessive enclitic is incorporated, the most optimal strategy to comply with this alignment requirement is to build an internally layered ternary foot and delete the last syllable of the host noun, stress shift being excluded.